KEGIATAN MEMBATIK ECOPRINT UNTUK PERKEMBANGAN SENI ANAK USIA DINI - Aam Kurnia; Nano Nurdiansah; Kiki Kilma Rihani (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
Based on the background of art development research in group B RA Al-Husna shows that children's learning is still teacher-centered, even though the learning model used in this school is a group learning model. However, children are not free to choose activities according to their interests. The purpose of this study was to find out: (1) The reality of children's activities in ecoprint batik activities in group B RA Al-Husna; (2) The reality of the development of art group B RA Al-Husna; and (3) The reality of the relationship between ecoprint batik and the development of early childhood art in RA Al-Husna. This research is a quantitative research with a correlational research approach to find the relationship between variable X (Ecoprint Batik Making Activities) with variable Y (Art Development). Data collection techniques in this study were obtained through observation, performance, and documentation techniques. Then the data is analyzed using partial analysis of items per indicator, normality test, linearity test, correlation coefficient, and hypothesis test. The results showed that ecoprint batik activities were in the very good category with a value of 88.80 and the development of early childhood art in the very good category with a value of 84.88. The contribution given to variable X (ecoprint batik activities) to variable Y (early childhood art development) was 49% and the other 51% was influenced by other factors that were not examined in our PKM